22a. Answer: y' = 90x + 33
<u>Step-by-step explanation:</u>
y = 5u² + u - 1 u = 3x + 1
First take the derivative of y = 5u² + u - 1 with respect to u ![\bigg(\dfrac{dy}{du}\bigg)](https://tex.z-dn.net/?f=%5Cbigg%28%5Cdfrac%7Bdy%7D%7Bdu%7D%5Cbigg%29)
y' = (2)(5u)(u') + (1)(u') - 0
= (10u)u' + u'
Next, take the derivative of u = 3x + 1 with respect to x ![\bigg(\dfrac{du}{dx}\bigg)](https://tex.z-dn.net/?f=%5Cbigg%28%5Cdfrac%7Bdu%7D%7Bdx%7D%5Cbigg%29)
u' = 3 + 0
u' = 3
Now, input u = 3x + 1 and u' = 3 into the y' equation:
y' = (10u)u' + u'
= 10(3x + 1)(3) + 3
= 30(3x + 1) + 3
= 90x + 30 + 3
= 90x + 33
***********************************************************************
22b. Answer: ![\bold{y'=-\dfrac{4}{(2x+3)^{3}}}](https://tex.z-dn.net/?f=%5Cbold%7By%27%3D-%5Cdfrac%7B4%7D%7B%282x%2B3%29%5E%7B3%7D%7D%7D)
<u>Step-by-step explanation:</u>
u = 2x + 3
![\text{We can rewrite y as }y=u^{-2}\\\text{Take the derivative of }y=u^{-2}\text{ with respect to u}\ \bigg(\dfrac{dy}{du}\bigg)\\\\y'=(-2)(u^{-3})(u')](https://tex.z-dn.net/?f=%5Ctext%7BWe%20can%20rewrite%20y%20as%20%7Dy%3Du%5E%7B-2%7D%5C%5C%5Ctext%7BTake%20the%20derivative%20of%20%7Dy%3Du%5E%7B-2%7D%5Ctext%7B%20with%20respect%20to%20u%7D%5C%20%5Cbigg%28%5Cdfrac%7Bdy%7D%7Bdu%7D%5Cbigg%29%5C%5C%5C%5Cy%27%3D%28-2%29%28u%5E%7B-3%7D%29%28u%27%29)
Next, take the derivative of u = 2x + 3 with respect to x ![\bigg(\dfrac{du}{dx}\bigg)](https://tex.z-dn.net/?f=%5Cbigg%28%5Cdfrac%7Bdu%7D%7Bdx%7D%5Cbigg%29)
u' = 2 + 0
u' = 2
Now, input u = 2x + 3 and u' = 2 into the y' equation
![y'=(-2)(2x+3)^{-3}(2)\\\\y'=-4(2x+3)^{-3}\\\\y'=-\dfrac{4}{(2x+3)^{3}}](https://tex.z-dn.net/?f=y%27%3D%28-2%29%282x%2B3%29%5E%7B-3%7D%282%29%5C%5C%5C%5Cy%27%3D-4%282x%2B3%29%5E%7B-3%7D%5C%5C%5C%5Cy%27%3D-%5Cdfrac%7B4%7D%7B%282x%2B3%29%5E%7B3%7D%7D)